Representasi Mitos Kebahagiaan Keluarga dan Krisis Paruh Baya dalam Film American Beauty - Romadhon, Ghifari Zaka; Ritonga, Muslimin; Saputra, Sepriadi (Edutik : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
This study aims to analyze the representation of the myth of family happiness and midlife crisis in the film American Beauty (1999) using Roland Barthes' semiotic analysis. The research approach used is descriptive qualitative, with the object of study being relevant scene excerpts related to the research focus. Data was collected through documentation and analyzed using Barthes' three levels of meaning: denotation, connotation, and myth. The results of the study indicate that the myth of family happiness is represented through the image of an ideal family that appears harmonious on the surface but harbors emotional distance and internal conflict. The midlife crisis is represented through the character of Lester Burnham, who experiences boredom, loss of identity, and rebellion against the routine of life. These two issues are interrelated, where the myth of family happiness creates social pressure that triggers the midlife crisis, while the crisis exposes the illusion behind the image of the ideal family. This study concludes that American Beauty not only represents social reality but also critiques Western popular culture's construction of family happiness and the midlife phase, emphasizing that happiness is subjective and does not always align with social standards.